Preload maintenance protects against a depression in left ventricular systolic, but not diastolic, function immediately after ultraendurance exercise. Issue 6 (17th March 2006) - Hassan, M Y; Noakes, T D; Berlyn, P; Shave, R; George, K
Abstract : Objective: To investigate indices of left ventricular (LV) function before and after a 224 km Ironman triathlon, specifically in the presence of unaltered haemodynamic loading. Method: LV loading and function were assessed before and after the race using M mode and Doppler echocardiography in 39 (mean (SD) age 33 (8) years, body mass 77.6 (8.6) kg; 36 male) triathletes in the Trendelenburg position. Specifically left ventricular end diastolic volume (LVEDV) was assessed to estimate preload, and systolic blood pressure to estimate afterload as well as heart rate (HR). Systolic functional indices included ejection fraction (EF) and the end systolic pressure/volume ratio (ESPV), and diastolic functional indices included peak mitral flow velocity in early (E) and atrial (A) filling as well as the ratio E/A. Data obtained before and after the race were compared by t tests, and delta LV functional indices were correlated with delta heart rate. Results: Preload (LVEDV: 143 (34) ml before v 147 (34) ml after) and afterload (systolic blood pressure 121 (13) v 115 (20) mm Hg) were not significantly altered after the race (p>0.05), nor were EF (61 (8)% v 58 (10)%) and ESPV (2.4 (0.9) v 2.1 (0.8) mm Hg/cm 3 ). The diastolic filling ratio E/A was significantly reduced after the race (1.73 (0.25) v 1.54 (0.23); p<0.05) due primarily to a reduction in E. HR was significantly higher after the race (57 (9) v 75 (8) beats/min; p<0.05), but delta HR was not related to delta E/A (p>0.05). Conclusion: When preload and afterload are unaltered after the race, because of the adoption of a unique assessment posture, LV systolic function is not depressed. A depression in LV diastolic function persists which is not explained by an increase in heart rate after the race.